Sleep Duration and Self-Rated Health are Independently Associated with Physical Activity Level in the Korean Population. - Kang-Ok Cho (Tehran University of Medical Sciences, 2014)
The purpose of this study was to examine the relationship of physical activity levels with sleep duration (SD), and self-rated health (SRH) using the fifth Korean National Health and Nutrition Examination Survey data from 2010 and 2011.Overall, 12,188 Korean people were evaluated in relation to meeting guidelines for vigorous PA (MVPA), moderate PA (MMPA), and low PA (MLPA) associated with SD and SRH.The adjusted odds ratio (AOR) of males who slept seven hours with MMPA (AOR=0.84) and MLPA (AOR=0.85) and eight hours with MMPA (AOR=0.76) and MLPA (AOR=0.78) significantly decreased compared to subjects who sleep 6 hours/day. In females, an AOR of less than 5 (AOR=1.40) and 6 hours (AOR=1.12) with MVPA was significantly increased compared to 7 hours sleep/day, while sleeping more than 8 hours/day was significantly decreased with MLPA (AOR=0.73). Compared to the very good SHR, the AORs of more negative SHR status with MVPA, MMPA, and MLPA in males and with MMVP and MLVP in females decreased significantly.Sleeping 6-8 hours/day for MMPA and MLPA in males and 7-8 hours/day for MVPA and MLPA in females, and a very good SRH for MVPA, MMPA, and MLPA in males and for MMPA and MLPA in females are recommended to participate physical activity for the Korean population. We therefore, the independent association between PA levels and SD or SRH according to gender supports public health program to participate physical activity for the Korean population.